IMPLEMENTASI KEBIJAKAN RUANG TERBUKA HIJAU DI KOTA ADMINISTRASI JAKARTA UTARA PROVINSI DKI JAKARTA - Hendra Wijayanto; Ratih Kurnia Hidayati (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
City Government of Jakarta, especially Government of North Jakarta as the authorized party has critical role in managing green open space in accordance with Law No. 26/2007 on Green Open Space Arrangement. The presence of green open space is needed as a climate regulator so that the air and water circulation system can be well maintained to support the embodiment of healthy and sustainable city, as a shade, oxygen producer, rainwater absorber, provider of animal habitat, pollutant absorbent, and windbreak. Green open space can improve ground water quality, prevent flooding, reduce air pollution, and lower city temperatures. In addition, green open space can also be a place of recreation, media communications for citizens of the city, as well as an object of education, research, and training in studying nature. This study aims to analyze the implementation of Green Open Space policy in the area of Jakarta particularly in North Jakarta. This research is a qualitative descriptive research that aims to provide a systematic, thorough, detailed, and profound analysis of the implementation of green open space management in North Jakarta. Data collection techniques were conducted with interviews supported by data collection through document review and observation. This research uses qualitative interactive data analysis technique which includes data reduction, data presentation, and conclusion / verification. The data validity test is done by using source triangulation. The results present that the implementation of the provision of green open space in North Jakarta Administration City is still not optimal and realized by 5% due to the use of land available for RTH does not function as the designation and the existence of some obstacles faced as weak supervision, land prices are expensive, improvement of undeveloped land and the lack of dissemination to the public. Therefore, this study recommend the need for a political will from the government, a review by the government to make Jakarta just as central government alone, and a tighter control by enforcement strict sanctions.DOI: https://doi.org/10.26905/pjiap.v2i1.1422